Text on back in Dutch: 'Owen Young, the temporary General-representative for the control on the Reparations according to the Dawes-plan...' (1928)
Text on back in Dutch: 'Owen Young, the temporary General-representative for the control on the Reparations according to the Dawes-plan...'.